2005
DOI: 10.1152/japplphysiol.01015.2004
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol aids resistance exercise in reducing unloading-induced ankle extensor strength losses

Abstract: While resistance exercise (REX) reduces ankle extensor (AE) mass and strength deficits during short-term unloading; additional treatments, concurrently administered with REX, are required to attenuate the greater losses seen with longer unloading periods. Subjects performed left leg REX, which otherwise refrained from ambulatory and weight-bearing activity for 40 days, while randomized to a capsule (placebo, albuterol) dosing regimen with no crossover to note whether albuterol helps REX mitigate unloading-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…T he knee extensors are a muscle group prone to space flight-induced mass and strength losses (8,16). Greater losses generally occur with longer flights, with the rate of strength loss exceeding that for muscle atrophy (7,16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T he knee extensors are a muscle group prone to space flight-induced mass and strength losses (8,16). Greater losses generally occur with longer flights, with the rate of strength loss exceeding that for muscle atrophy (7,16).…”
Section: Introductionmentioning
confidence: 99%
“…The device in Figure 1, which operates without gravity, offers more eccentric resistance than standard free weight equipment (5). The merits of the flywheel ergometer (FERG) to reduce strength losses in a 40-day ground-based microgravity analog were assessed and showed that the device offered a substantial mechanical load stimulus to the unloaded knee extensors (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When therapeutic oral b 2 agonist and REX treatments were combined in a disuse atrophy model, they increased bone mineral content and muscle strength to an unloaded limb (8,9). The treatments may cause greater relative strength gains in disuse models than in healthy humans due to higher b 2 receptor density or sensitivity (2,15,27).…”
Section: Introduction Bmentioning
confidence: 99%
“…The impact of oral b 2 agonist and REX treatments upon KE strength changes over 40 days of ULLS were recently examined (9). Two groups performed unloaded KE REX 3 days per week.…”
Section: Introduction Bmentioning
confidence: 99%